Redox Regulation of UDP-glucose Pyrophosphorylase from Entamoeba histolytica - Martínez, Lucila Inés (2011)
Amoebiasis is an intestinal infection caused by the human pathogen Entamoeba histolytica and representing the third leading cause of death by parasites in the world. Host-parasite interactions mainly involve anchored glycoconjugates localized in the surface of the parasitic cell. In protozoa, synthesis of structural oligo- and polysaccharides occurs via UDP-glucose, generated in a reaction catalyzed by UDP-glucose pyrophosphorylase. We report the molecular cloning of the gene coding for this enzyme from genomic DNA of E. histolytica and its recombinant expression in Escherichia coli cells. The purified enzyme was kinetically characterized, catalyzing UDP-glucose synthesis and pyrophosphorolysis with V(max) values of 95 U/mg and 3 U/mg, respectively, and affinity for substrates comparable to those found for the enzyme from other sources. Enzyme activity was affected by redox modification of thiol groups. Different oxidants, including diamide, hydrogen peroxide and sodium nitroprusside inactivated the enzyme. The process was completely reverted by reducing agents, mainly cysteine, dithiothreitol, and thioredoxin. Characterization of the enzyme mutants C94S, C108S, C191S, C354S, C378S, C108/378S, M106S and M106C supported a molecular mechanism for the redox regulation. Molecular modeling confirmed the role of specific cysteine and methionine residues as targets for redox modification in the entamoebic enzyme. Our results suggest that UDP-glucose pyrophosphorylase is a regulated enzyme in E. histolytica. Interestingly, results strongly agree with the occurrence of a physiological redox mechanism modulating enzyme activity, which would critically affect carbohydrate metabolism in the protozoon.